2018
DOI: 10.3233/jad-170601
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Iron in the Pathogenesis of Multiple System Atrophy: A Viewpoint

Abstract: Iron is essential for cellular development and maintenance of multiple physiological processes in the central nervous system. The disturbance of its homeostasis leads to abnormal iron deposition in the brain and causes neurotoxicity via generation of free radicals and oxidative stress. Iron toxicity has been established in the pathogenesis of Parkinson’s disease; however, its contribution to multiple system atrophy (MSA) remains elusive. MSA is characterized by cytoplasmic inclusions of misfolded α-synuclein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 208 publications
(113 reference statements)
1
52
1
Order By: Relevance
“…Moreover, it indicates new strategies to develop brain-targeted metal chelators. Iron chelators have been deemed therapeutically useful in PD and other neurodegenerative conditions (Dunaief 2011;Joppe et al 2019;Kaindlstorfer et al 2018;Ndayisaba et al 2019). However, their exact effects on brain pathophysiology have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it indicates new strategies to develop brain-targeted metal chelators. Iron chelators have been deemed therapeutically useful in PD and other neurodegenerative conditions (Dunaief 2011;Joppe et al 2019;Kaindlstorfer et al 2018;Ndayisaba et al 2019). However, their exact effects on brain pathophysiology have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Iron can convert native αS into a β-sheet conformation and promotes/accelerates its aggregation either directly or via increasing levels of oxidative stress. Interestingly, αS has been identified to have a ferrireductase activity and an iron-regulated element on mRNA level, implying a direct interaction between iron and αS [ 302 ].…”
Section: Neuropathologymentioning
confidence: 99%
“…TfR expression was unchanged in pons and SN in PD, MSA, and controls, while putamen showed decreased TfR expression in PD compared to controls and MSA. The results of this study suggest that neurodegeneration is accompanied by region-specific differences in iron dysregulation which might be regarded as disease specific patterns in MSA, where limited iron export coupled with an increase in ferritin iron load results in decreased bioavailability of iron in MSA pons [ 302 ]. A dysregulation of iron export coupled with an increase in ferritin iron was detected to a lesser extent also in putamen.…”
Section: Neuropathologymentioning
confidence: 99%
See 1 more Smart Citation
“…For PD, an iron overload with its inherent toxicity for dopaminergic neurons of the SN is assumed to play an important role in the disease pathogenesis [40]. Concerning MSA and PSP, pathological studies have demonstrated an increase of iron levels in the putamen and globus pallidus but also in the SN [47,48]. So far, there are no studies investigating the cellular and extracellular changes in PD patients with LN hyperechogenicity.…”
Section: Discussionmentioning
confidence: 99%